Endothelin as a causative factor of blunted volume reflex in diabetic rats - Wongmekiat O. (2014)
1. The study investigated whether endothelin (ET) contributed to the diabetes-associated alterations in volume reflex and characterised the receptor subtype that might be involved. The influence of renal sympathetic nerves on these aspects of ET was also examined. 2. Groups of nondiabetic and streptozotocin-induced diabetic rats were subjected to an acute isotonic saline volume expansion (VE), 10% body wt in the presence and absence of ET antagonists. 3. Cumulative urine sodium excretion (CuUNaV) after VE in diabetic rats reached values of 116±10 in the denervated and 74±6 μmol min-1 g kidney wt-1 in the innervated kidneys, which were both less (both P<0.001) than those achieved in the nondiabetic rats, at 267±9 in the denervated and 183±10 μmol min-1 g kidney wt-1 in the innervated kidney, respectively. 4. Diabetic rats pretreated with a nonselective ETA/ETB antagonist had an enhanced CuUNaV in the denervated kidneys by 37% (P<0.01) compared to that of untreated diabetic rats. At both doses of SB209670 these increments were less than the values obtained previously in nondiabetic rats (both P<0.01). The ETA/ETB antagonist had no meaningful effect on CuUNaV in the innervated kidneys of the diabetic rats, whereas previous studies in nondiabetic rats showed the response to be depressed. The CuUNaV responses to VE in diabetic rats given the selective ETA antagonist were not different from those observed in untreated diabetic rats, irrespective of whether or not the renal nerves were present. In nondiabetic rats, the ETA antagonist had an action similar to the mixed antagonist. 5. These findings demonstrate that activation of ETB receptors contributes to the depressed ability to excrete a saline load in diabetes mellitus, but its impact is obscured by the influence of the renal nerves.